Effect of weld parameter on mechanical and metallurgical properties of dissimilar joints AA6082–AA6061 in T6 condition produced by FSW - H. S. Patil; S. N. Soman (Fracture and Structural Integrity)
The effect of processing parameters on the mechanical and metallurgical properties of dissimilar joints of AA6082–AA6061 produced by friction stir welding was analysed in this study. Different FSW samples were produced by varying the welding speeds of the tool as 50 and 62 mm/min and by varying the alloy positioned on the advancing side of the tool. In all the experiments the rotating speed is fixed at 1600rpm. All the welds were produced perpendicularly to the rolling direction for both the alloys. Microhardness (HV) and tensile tests performed at room temperature were used to evaluate the mechanical properties of the joints. In order to analyse the microstructural evolution of the material, the weld’s cross-sections were observed optically and SEM observations were made of the fracture surfaces. The corrosion tests of base alloy and welded joints were carried out in 3.5%NaCl solution at a room temperature. Corrosion current and potential were determined using potentiostatic polarization measurements. It was found that the corrosion rates of welded joints were higher than that of base alloy.